PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA GURU YANG DIMODERASI GAYA KEPEMIMPINAN KEPALA SEKOLAH PADA GURU SMP NEGERI DI KECAMATAN BATANG - Kusmiati, 12.5202.0125; Basiya, R. (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze Influence of Work Motivation and Discipline Against Teacher Performance Moderated Principal Leadership Styles On Secondary Schools Teachers in District Trunk. In this study population of all teachers in the district of Batang junior civil servants, while the sample used as many as 149 respondents with a sampling technique. With the criteria of the respondents are civil servants Teachers in Secondary Schools Kecematan Batang, Batang. Measurements using a Likert scale with 5 (five) alternative answers. Test instrument used is the validation and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Motivation positive and significant impact on teacher performance, (ii) Work Discipline positive and significant impact on teacher performance, (iii) the principals leadership style has no effect on teacher performance, (iv) Style Principal leadership has no effect on work motivation against performance Teachers, (v) the principals leadership style had no effect on performance erhadap Work Discipline Master. Keywords: Work Motivation, Work Discipline, Teacher Performance, and Principal Leadership Styles